A comparison of three organisational levels in one health care region in Sweden implementing person-centred care: coupled, decoupled or recoupled in a complex organisation - Malin Tistad; Lars Wallin; Eric Carlström (BMC, 2022)
Abstract Background Establishing more substantial patient involvement in the health care has become fundamental to Western health care services. Person-centred care (PCC) has been developed as a way of working that involve the patients and family members. However, the implementation of PCC in clinical practice has proven to be challenging. The aim of this study was to explore the congruence of managers' perceptions and understanding of various aspects of PCC across three organisational levels in one health care region in Sweden in terms of coupling, decoupling and recoupling. Methods A policy on increased patient participation in health care was adopted in one health care region in Sweden. This policy was embodied in the form of PCC and a support strategy for the implementation was put in place. Participants representing three organisational levels (senders: politicians, n = 3; messengers: senior management, n = 7; and receivers: middle- and frontline managers, n = 13) were interviewed and documents collected. A deductive qualitative content analysis was performed and findings from the three organisational levels compared. Results Descriptions of PCC at all the three organisational levels included health care provided in partnership between provider and patient. However, messengers and receivers also included aspects of how work was organised as part of the concept. Representatives at all levels expected high-quality care while reducing health care costs as an outcome, however, messengers and receivers also anticipated improvements in the work environment and reduced staff turnover. Strategies to support implementation included continuation and enhancement of existing routines that were considered person-centred and development of new ones. A need to make PCC less 'fuzzy' and ambiguous and instead communicate a more tangible care process was described. Representatives among messengers and receivers also suggested that no actions were needed because the practice was already considered person-centred. Conclusion The findings indicated that congruence between organisational levels existed in some aspects, suggesting coupling between policy and practice. However, also incongruences were identified that might be due to the fuzziness of definitions and the application of PCC in practice, and the difficulty in assessing the level of patient-centredness in clinical practice.